2016
DOI: 10.1152/ajpgi.00047.2016
|View full text |Cite
|
Sign up to set email alerts
|

Legumain is activated in macrophages during pancreatitis

Abstract: Pancreatitis is an inflammatory disease of the pancreas characterized by dysregulated activity of digestive enzymes, necrosis, immune infiltration, and pain. Repeated incidence of pancreatitis is an important risk factor for pancreatic cancer. Legumain, a lysosomal cysteine protease, has been linked to inflammatory diseases such as atherosclerosis, stroke, and cancer. Until now, legumain activation has not been studied during pancreatitis. We used a fluorescently quenched activity-based probe to assess legumai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…up-regulated in pIC group of FO5 at 24 HPS); however, qPCR showed that the expression of this transcript significantly increased in the pIC group of FO5 at 6 HPS compared to that of FO7. lgmn is associated with macrophage activity and differentiation in mammals [ 61 , 62 ], and it has been shown to be more highly expressed in mature macrophages compared with less differentiated stages (early progenitors and monocytes) in goldfish [ 63 ]. If lgmn function is conserved in mammalian and teleost macrophages, then our lgmn expression results suggest that dietary fish oil (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…up-regulated in pIC group of FO5 at 24 HPS); however, qPCR showed that the expression of this transcript significantly increased in the pIC group of FO5 at 6 HPS compared to that of FO7. lgmn is associated with macrophage activity and differentiation in mammals [ 61 , 62 ], and it has been shown to be more highly expressed in mature macrophages compared with less differentiated stages (early progenitors and monocytes) in goldfish [ 63 ]. If lgmn function is conserved in mammalian and teleost macrophages, then our lgmn expression results suggest that dietary fish oil (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The potential role and limitations of legumain as a biomarker was discussed in an editorial in the same issue of Atherosclerosis [282] as paper II. Legumain has also been suggested as biomarker for liver fibrosis [283] and pancreatitis [284]. A biomarker is defined as "a characteristic that is objectively measured and evaluated as an indicator of normal biological processes, or pharmacological responses to a therapeutic intervention" [285].…”
Section: Clinical Relevance Of Legumainmentioning
confidence: 99%
“…In pancreatic cancer, it was noted that AEP exists in exosomes and that AEP-harboring exosomes potentiate phosphoinositide 3-kinase (PI3K) signaling pathways, causing enhanced invasion ability of exosome-receiving cells [38] (Figure 1 and Table 1). Intriguingly, patients with chronic pancreatitis, one of the causes of pancreatic cancer, show the high levels of AEP in macrophages [39]. Furthermore, AEP is detected in stroma and endothelial cells in pancreatic cancer tissues [40].…”
Section: Aepmentioning
confidence: 99%